Utilization of coconut shell pyrolysis oil diesel blends in a direct injection diesel engine. (2021) - Gunasekar, N.; Mohan, C.G.; Prakash, R.; Saravana Kumar, L.
Abstract: Burning fossil fuels has serious and long-standing negative effects on public health, local communities and ecosystems, and the global climate. This requires an urge to identify suitable methods to reduce emissions or by the usage of alternate fuels which is less harmful to the environment. This paper utilizes the opportunity to find the ability of the pyrolysis oil obtained from coconut shell and diesel blends to replace fossil diesel in a compression ignition engine. For this purpose, a batch type fixed bed pyrolysis reactor was designed and fabricated. The different blends such as 10% coconut shell pyrolysis oil blend with diesel and 20% coconut shell pyrolysis oil blend with diesel and diesel fuel are used to carry out the experiments. From the results, it was found that the performance parameters are comparable and the harmful-emissions reduction is better than diesel operation. It was found that in 20% coconut shell pyrolysis oil blend with diesel, there is a reduction of 27.7%, 23.5%, 7.9% and 13.3% in unburned hydrocarbon, carbon monoxide, oxides of nitrogen and smoke emissions respectively when the levels are measured against that of a diesel fuel engine.